Fabrication of novel transparent Co3O4-TiO2 nanowires p-n heterojunction diodes for multiband photodetection applications - Choudhuri, Bijit; Mondal, Aniruddha; Dwivedi, Shyam Murli Manohar Dhar; Henini, Mohamed (Elsevier, 2017)
Axial Co3O4 - TiO2 heterojunction nanowires (NWs) were synthesized by glancing angle deposition (GLAD) technique. The p-n heterojunction showed excellent rectification ratio of 2.26 × 102 at ± 3.4 V. The forward turn on voltage of 1.5 V in the dark was reduced to 1 V under white light excitation on the device. The diode showed a maximum half-wave rectification efficiency of 7.77% at 200 Hz frequency operated with maximum ±10 V. The device showed maximum peak responsivity of 4.01 A/W and internal gain of 13.1 at 380 nm wavelength. The detectivity was calculated to be 2.82 × 1011 and 1.69 × 1011 Jones and the noise equivalent power was estimated to be 14.9 and 24.8 pW at 380 and 620 nm wavelength, respectively. The device spatial response showed sharp transition with rise and fall time of ∼0.17s and 0.21s, respectively.